Effect of probiotic Lactobacillus plantarum CM49 on microbial profile and lactobacilli counts in milk of mastitic cattle - Muhammad Zeeshan Izhar; Muhammad Nawaz; Tahir Yaqub; Muhammad Avais (BMC Microbiology)
Abstract Background Bovine mastitis is a common udder disease in cattle, mainly caused by bacteria and other infectious agents. Traditionally antibiotics are used for their treatment, but the development of antibiotic resistance has increased the importance of using non antibiotic alternative such as probiotic. In current study a previously in vitro characterized isolate Lactobacillus plantarum CM49 infused into two groups of cattle suffering from clinical mastitis (n = 5) and sub-clinical mastitis (n = 5). Results The bacterial composition and diversity analysis of milk samples before and after probiotic administration was analyzed using 16S rRNA gene base metagenomic analysis and lactobacillus counts were also evaluated using Real time PCR. The results show that there was an increase in abundance of Proteobacteria and decrease in Firmicutes at phylum level in both groups while major mastitogens genera Staphylococcus and Streptococcus abundance was reduced after treatment in sub-clinical mastitis group (SCMG) and clinical mastitis group (CMG) respectively. Lactobacilli counts evaluated through Real time PCR showed an increase in number, furthermore diversity indices showed an increase in diversity after treatment with probiotic. Conclusion It is concluded from the results that Lactobacillus plantarum CM49 may serve as promising candidate for improving dysbiosis resulting from mastitis and improving microbial diversity.